Economic Value of Environmental Services of Swamp Land Ecosystem (A Case Study in the Hulu Sungai Utara Regency, Kalimantan Selatan) - Hamadani Hamdani; Djoko Santoso; Rifiana Rifiana (TROPICAL WETLAND JOURNAL, 2022)
About 22,000 hectares are planned to be converted to oil palm plantations by the local government. However, this area has been the source of livelihood for the Banjar people for generations. This economic-environmental services valuation was carried out using a total valuation approach. Previous studies have shown that swamps have economic benefits as a source of water for rice farming (Oryza sativa), timber (Melaleuca cajuputi), fisheries, handicraft crops (Eleocharis dulcis), and for drinking water. They also have ecological benefits in biological functions such as fish feed and breeding grounds, Galam (Melaleuca leucadendron) breeding, water storage, carbonate stocks, and biodiversity value. The total economic value was 21.3 million IDR per ha, with a ratio of the economic value of 7.15% and the value of ecosystem services (ecological) of 92.85%.